2017
DOI: 10.4172/2155-6148.1000720
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Nephrolithotomy under Thoracic Paravertebral Block: A Preliminary Report

Abstract: Background: The second look percutaneous nephrolithotomy (PCNL) is usually done under general anesthesia. Thoracic paravertebral block has been shown to provide sufficient postoperative analgesia for a variety of thoracic and upper abdominal surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…conducted a study on second look PCNL where conscious sedation using dexmedetomidine and paravertebral block was used for anesthesia and postoperative analgesia. [ 26 ] The average time for first rescue analgesia in the postoperative period was 15 ± 3.9 hours compared to 17.22 ± 0.97 hours in ESPB patients in our study. Lönnqvist et al .…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…conducted a study on second look PCNL where conscious sedation using dexmedetomidine and paravertebral block was used for anesthesia and postoperative analgesia. [ 26 ] The average time for first rescue analgesia in the postoperative period was 15 ± 3.9 hours compared to 17.22 ± 0.97 hours in ESPB patients in our study. Lönnqvist et al .…”
Section: Discussionmentioning
confidence: 55%
“…in their case series found that patients with PVB to be satisfied in postoperative period. [ 26 ] However, since no data comparing ESPB with PVB are available, we cannot edge ESPB over PVB but is definitely providing better postoperative pain relief than conventional opioid-based or opioid-free analgesia.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary objectives were postoperative pain scores and analgesic consumption, which were recorded up to 48 h postoperatively, ease of block performance and time taken to perform the block, which was noted during the block performance. An earlier study on PVB indicated that the mean (standard deviation [SD]) duration of analgesia following PVB for PCNL was 15 (3.9) h.[ 9 ] For a 20% change in duration of analgesia with 80% power and an α-error of 0.05, we calculated that 27 patients were needed in each group. Considering possible dropouts, we planned to include 30 patients in each group.…”
Section: Methodsmentioning
confidence: 99%
“…Using PASS program, setting alpha error at 5% and power 80%. Result from previous study [13] Based on this the needed sample we recruited 100 cases for the study.…”
Section: Sample Sizementioning
confidence: 99%